Przemoc domowa = Domestic violence - Celina Łepecka-Klusek; Agnieszka Konstancja Pawłowska-Muc; Anna Bogusława Pilewska-Kozak; Grażyna Stadnicka; Klaudia Pałucka (Kazimierz Wielki University, 2015)
Łepecka-Klusek Celina, Pawłowska-Muc Agnieszka Konstancja, Pilewska‑Kozak Anna Bogusława, Stadnicka Grażyna, Pałucka Klaudia. Przemoc domowa = Domestic violence. Journal of Education, Health and Sport. 2015;5(6):169-182. ISSN 2391-8306. DOI 10.5281/zenodo.18420 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A169-182 https://pbn.nauka.gov.pl/works/564476 http://dx.doi.org/10.5281/zenodo.18420 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015.   Przemoc domowa Domestic violence   Łepecka-Klusek Celina1, Pawłowska-Muc Agnieszka Konstancja2, Pilewska‑Kozak Anna Bogusława1, Stadnicka Grażyna3, Pałucka Klaudia4   1Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Al. Racławickie 23 2Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 3Samodzielna Pracownia Umiejętności Położniczych Uniwersytet Medyczny w Lublinie, ul. Staszica 4/6 4Doktorantka w Katedrze i Klinice Ginekologii i Endokrynologii Ginekologicznej Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, Al. Racławickie 23 1Department and Clinic of Gynaecology and Gynaecological Endocrinology, School of Health Studies, Medical University of Lublin, Al. Racławickie 23 2Postgraduate Training Centre for Nurses and Midwives, Dr Tytus Chałubiński Specialist Hospital in Radom, ul. Lekarska 4 3Independent Obstetric Skills Workshop, Medical University of Lublin, ul. Staszica 4/6 4Doctoral Candidate at the Department and Clinic of Gynaecology and Gynaecological Endocrinology, School of Health Studies, Medical University of Lublin, Al. Racławickie 23   Adres do korespondencji: Celina Łepecka-Klusek Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej Wydział Nauk o Zdrowiu Uniwersytet Medyczny w Lublinie Al. Racławickie 23 20-049 Lublin, Poland tel./fax. 81-7183286 e-mail: cklusek@onet.pl   Przemoc domowa Streszczenie Wprowadzenie. W każdej społeczności na świecie żyją osoby, które doświadczyły w swoim życiu różnych form przemocy domowej.  Media dość często przekazują informacje o nich, niekiedy jednak zbyt późno, czyli w sytuacji, gdy doszło już do tragedii. Cel pracy. Ukazanie zjawiska przemocy domowej jako wciąż aktualnego, trudnego do zdiagnozowania i rozwiązania problemu. Skrócony opis stanu wiedzy. W opracowaniu zdefiniowano określenia: przemoc domowa oraz przemoc w rodzinie, które dość często w piśmiennictwie używane są zamiennie. Omówiono typy i cykle przemocy oraz skalę zjawiska nie tylko w Polsce, określając ją jako trudną do rzetelnego oszacowania. Podkreślono, iż najczęściej odbywa się ona w domu i stosowana może być wobec wszystkich domowników. Zróżnicowano także czynniki ryzyka oraz scharakteryzowano ofiary, jak i cechy sprawców przemocy domowej. Podsumowanie. Analiza piśmiennictwa pokazała, iż przemoc domowa nie może być niezauważona. Niewątpliwie ona istnieje, pomimo chęci, zwłaszcza ze strony ofiar, ukrycia jej. W wymiarze ogólnopolskim ma nawet w ostatnich latach tendencją wzrostową. Dlatego ważne są działania zapobiegawcze, z udziałem całego społeczeństwa.   Słowa kluczowe: przemoc domowa, przemoc w rodzinie.   Domestic violence Summary Introduction. In every community in the world there live people who has experienced different acts of domestic violence in their life. Media quite often provide information about them, however sometimes too late, i.e. in a situation where there was already a tragedy. Aim of the study. Showing the phenomenon of domestic as a perennial problem, difficult to be diagnosed and solved. Brief description of the state of the art. The terms: domestic violence and family violence were defined in the study, and are very often used interchangeably in the literature. The types and cycles of violence and the scale of this phenomenon not only in Poland were discussed, formulating the opinion that the phenomenon is hard to be realistically assessed. It was emphasized that it usually happens at homes and can be used towards all family members. Also risk factors were diversified as well as victims and perpetrators of domestic violence were characterized. Conclusion. Analysis of the literature showed that domestic violence cannot be unnoticed. With no doubt it exists, despite the desire, especially on the part of the victims, to hide it. In terms of nationwide dimension, there is even a growth tendency in the last years. They are therefore important preventive actions, with the participation of the whole society.   Keywords: domestic violence, family violence.